Trying to Measure Local Well-Being: Indicator Development as a Site of Discursive Struggles. (June 2013) - Scott, Karen; Bell, Derek
The New Labour government in the UK encouraged all local authorities to develop quality-of-life indicators. Development of these indicators was intended to engage local people in a shared vision for their area and to effect improvements in local well-being and sustainability. However, international research has reported a failure of such instruments to generate concrete policy change. This paper reports on a three-year ethnographic study in one local authority in North East England which took a discursive approach to analysing indicator development. The research shows how indicator development acted as a 'site of struggle' between competing discourses. These discursive struggles may have hampered the development of a set of indicators, but they allowed different conceptions of well-being, participation, indicators, and the policy-making process to be discussed and deliberated, inducing discursive shifts in the political arena. Policy makers and scholars should therefore place more focus on the process of developing indicators rather than the indicators that are produced, as it is these which have the potential to produce longer term effects on policy making.